MEDIA PEMBELAJARAN MUSSCHENBROEK BERBASIS ARDUINO DENGAN RELAY DAN SENSOR MAX6675 UNTUK MENINGKATKAN HOTS DAN KREATIVITAS - Soka Hadiati; Adi Pramuda; Matsun Matsun (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to obtain a proper and effective form of Arduino-based Musschenbroek learning media with MAX6675 relays and sensors in increasing HOTS and student creativity, as well as knowing student responses to the developed Arduino-based Musschenbroek learning media with MAX6675 relays and sensors. This research is a development research with ten stages, including: information gathering research, planning, initial development, initial testing, main product revision, main testing, operational product revision, operational field testing, final product revision, and dissemination. The research subjects involved in the research, namely: experts, lecturers, colleagues, and students were selected by cluster random sampling technique. Analysis of the feasibility of learning media and student responses is determined qualitatively. The results showed that Arduino-based Musschenbroek learning media with relays and MAX6675 sensors in increasing HOTS and valid creativity with very good criteria. Students gave a very good response to learning media.